Transformasi Digital Perpustakaan : Mengadopsi Teknologi Terbaru untuk Meningkatkan Layanan - Rahman Pura; tafsir, muhammad; Idrus Stambul; Eva Marin Sambo; Bungatang; Gunawan Pongkapadang; Orfyanny S Themba; Muh. Irwan Nir Hamiddin; Jumiati Syam (STIE Amkop Makassar, Indonesia, 2024)
Digital transformation has brought a breath of fresh air to academic libraries. By adopting the latest technology, libraries are no longer just places to store books, but have metamorphosed into dynamic learning centers. The integration of technologies such as artificial intelligence, big data analysis, and virtual reality has enabled libraries to provide more personalized, efficient, and innovative services. However, the success of this digital transformation is highly dependent on infrastructure readiness, human resource competency, and ongoing policy support. This activity was carried out on July 17, 2024. The method used in this benchmarking was divided into three stages where the first stage was a visit to the Sultanah Zanariah and Raja Zarith Sofia libraries UTM Johor Bahru, Malaysia, then the second stage was a presentation from the speakers and the third stage was a sharing session. The results of this activity show that library digitalization can increase efficiency, expand the reach of services, and provide a more personalized user experience. However, this study also identified challenges such as the digital divide and the need for librarian competency development